Houses as collateral and household debt deleveraging in Korea - Joonhyuk Song; Doojin Ryu (Economics: The Open-Access, Open-Assessment Journal, 2021)
As Korea's household debt has increased rapidly since the mid-2000s, concerns that its economy's hard-wired leveraging may negatively impact economic activity have grown. Calls are being made for policy actions to return the economy to its long-run trend. Housing preferences and monetary shocks can both trigger deleveraging, as most household debt is profoundly connected to the housing market, and debt growth increases sensitivity to interest rates. Constructing a dynamic stochastic general equilibrium model with heterogeneous households and the housing production sector, we simulate and analyze the macroeconomic effects of deleveraging. Because a lower loan-to-value (LTV) ceiling limits the size of household debt, the deleveraging effect caused by borrowers' re-optimization is alleviated as the LTV ceiling decreases. When the housing price is included as an additional operating target in an otherwise standard monetary policy (MP) rule, economy-wide welfare increases when the MP is proactive to demand shocks and inactive to supply shocks. These findings suggest that deleveraging risk can be attenuated by adopting a lower LTV ceiling and maneuvering MP asymmetrically depending on the source of a shock.
Keywords: E31; E52; 330; collateral; deleveraging; emerging economy; household debt; loan-to-value ceiling; monetary policy rule